2019
DOI: 10.1007/s00424-019-02257-4
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary heart disease: pathophysiology, clinical presentation, and animal models of HCM, RCM, and DCM associated with mutations in cardiac myosin light chains

Abstract: Genetic cardiomyopathies, a group of cardiovascular disorders based on ventricular morphology and function, are amongst the leading causes of morbidity and mortality worldwide. Such genetically-driven forms of hypertrophic (HCM), dilated (DCM) and restrictive (RCM) cardiomyopathies are chronic, debilitating diseases that result from biomechanical defects in cardiac muscle contraction and frequently progress to heart failure (HF). Locus and allelic heterogeneity, as well as clinical variability combined with ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 139 publications
0
22
0
Order By: Relevance
“…Variants in MYL3 are rarely involved in familial cardiomyopathy, [4][5][6][7] and recessive LOF MYL3 variants, thus far, have not been described. The majority of reported variants are, however, associated with SCD at a young age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variants in MYL3 are rarely involved in familial cardiomyopathy, [4][5][6][7] and recessive LOF MYL3 variants, thus far, have not been described. The majority of reported variants are, however, associated with SCD at a young age.…”
Section: Discussionmentioning
confidence: 99%
“…Autosomal dominant and recessive variants in MYL3, which encodes the ventricular myosin essential light chain (ELC), are a rare cause of HCM with inter-and intrafamilial variability ranging from benign to malignant forms with cardiac failure and SCD. [3][4][5][6][7] It has also been suggested that MYL3 variants can result in variable morphological phenotypes. [7][8][9] There are, however, no reports of DCM associated with MYL3 variants or cardiomyopathy associated with likely ELC deficiency due to nonsense or essential splice acceptor variants in MYL3.…”
Section: Introductionmentioning
confidence: 99%
“…We go on to show that the CM in B6N may be due to a null mutation in myosin light chain kinase 3 (Mylk3), which is only present in B6N substrains. MYLK3 phosphorylates myosin light chain 2 (MYL2), which is itself essential for the assembly of actin fibres in the heart and mutated in many human cases of CM (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac morphological phenotypes of recessive MYL2 myopathy have shown no clear correlation with the genotype. 1,5) Reported patients from two Italian families and 8 Dutch families, all harboring mutations affecting the last exon, have invariably experienced premature death, although cardiac morphology ranged from hypertrophic, dilated to noncompaction cardiomyopathy. 1) Another sibling, homozygous of the P144Rfs*57 variant, showed the hypertrophic phenotype, well contrasting with the noncompaction morphology of the presented case.…”
Section: Discussionmentioning
confidence: 99%